Hak Imunitas Pemerintah Dalam Penanganan Pandemi Corona Virus Disease 2019 (Covid-19) (Analisis Pasca Putusan Mk No 37/Puu_Xviii/2020) - Hidayat*, Moh. Sobihul; Herisasono, Adi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Policy regulations are not a new phenomenon in governance in Indonesia. Policy regulations arise as a result of the needs of society that continue to grow so that it requires the government to take swift legal action, even ignoring the principle of legality or what is also known as wetmatigheid van bestuur. This study aims to explain the forms of impunity in article 27 of Law No.2/2020 before and after the issuance of the Constitutional Court Decision No.37/PUU-XVIII/2020, and analyze the implications for fulfilling the principle of Equality Before The Law. This research is normative. The data collection technique used is literature study. The results of the research show that article 27 of Law No.2/2020 gives birth to absolute impunity for law enforcement, this is contrary to the constitution because it has closed the space for carrying out legal proceedings against law violations. However, after the issuance of the Constitutional Court Decision No.37/PUU-XVIII/2020, the concept of absolute impunity has changed to the concept of Limited Impunity with 2 limitations, namely government actions are carried out based on (1) good faith and (2) in accordance with statutory regulations.